Peranan Marketing Mix Pada Hotel Syariah Solo - Alfista, Riza, Ahmad Mardalis, SE.,MBA (2017)
This study aims to know the role of marketing mix on purchase decisions at Hotel Syariah Solo. This study was a descriptive study. Thepopulation in this study are all sleepovers Hotel Syariah Solo. The sample in this study is 99 lodger Hotel Syariah Solo. Sampling by incidental sampling.The data used is primary and secondary data. The data collection technique using questionnaires on test t, the product contributes to the purchase decision, price does not play a role on purchasing decisions, place contributes to the purchase decision,promotion contributes to the purchase decision, process price does not play arole on purchasing decisions, people contributes to the purchase decision, physical evidence contributes to the purchase decision. Keywords: Product, Price, Place, Promotion, Process, People, Physical Evidence & Purchase Decision.